Kecemasan dan Prestasi Akademik Pada Mahasiswa Keperawatan Di Universitas Klabat - Sanger, Ailine Yoan; Lamboan, Dessy Anggraine (JUKEJ : Jurnal Kesehatan Jompa, 2025)
Abstract Academic achievement shows students' learning ability. One of the factors that can affect academic achievement is anxiety. The purpose of this study was to determine the relationship between anxiety and academic achievement among nursing students at Universitas Klabat. The method used was cross-sectional, with the Spearman's rho correlation statistical test. The sampling technique used the total sampling technique comprised of 143 samples, collected through a Google form questionnaire. The results showed that out of 143 respondents, 130 (90.9%) experienced moderate anxiety, 9 (6.3%) respondents experienced mild anxiety, and 4 (2.8%) respondents experienced severe anxiety. Then for academic achievement, it showed that out of 143 respondents, 109 (76.2%) were in the very good category and 34 (23.8%) respondents were in the good category. The results of the study on the relationship between anxiety and academic achievement in Nursing students at Klabat University found a p value of 0.356> 0.05 with a correlation coefficient value of r = -0.078, which means there is no significant relationship between anxiety and academic achievement. The recommendation in this study is that further research needs to be conducted involving other factors and it is better to add variables such as whether there is a relationship between anxiety and coping mechanisms. Keywords: Academic Achievement, Anxiety, Students